Evaluation of Surrogate Risk Factors for Severe Progression of COVID-19 in Tobacco Smoking Sub-Population and its Possible Amelioration by Immune Modulators (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: COVID-19; smoking; mechanical ventilation; hazard analysis and mycobacterium indicus pranii (MIP)